2015
DOI: 10.1044/2015_lshss-14-0084
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Language, Pragmatics, and Social Intervention in a Single-Subject Case Study of a Child With a Developmental Social Communication Disorder

Abstract: This clinical focus article demonstrates the complexity of needs in a child with an SCD and how these can be addressed in individualized intervention. Findings are discussed in relation to the essential nature of language support including pragmatic therapy for children with SCDs. Discussion of the role of formal and functional outcome measurement as well as the proximity of chosen outcomes to the intervention is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…The present results also may have been affected by clinical sampling, restricted age range, low family SES, maternal depressive symptoms and presence of intellectual disabilities and by not using more varied measures of language development (i.e. social responsiveness scale or social communication questionnaire) …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The present results also may have been affected by clinical sampling, restricted age range, low family SES, maternal depressive symptoms and presence of intellectual disabilities and by not using more varied measures of language development (i.e. social responsiveness scale or social communication questionnaire) …”
Section: Discussionmentioning
confidence: 85%
“…social responsiveness scale or social communication questionnaire). 34 Zero order correlations for the whole sample indicated that linguistic and intellectual development correlated with ER skills and maternal BDI scores in hypothesized directions, while controlling for receptive language scores removed all significant associations. Controlling for expressive language showed that EL was related with BDI, linguistic and development levels, while it correlated negatively with semantics of receptive language.…”
Section: Discussionmentioning
confidence: 94%
“…The Targeted Observation of Pragmatics in Children’s Conversation Observation scheme (TOPICC; Adams et al, 2010) was used to obtain an overall rating of the conversational competence of the child, including taking account of listener’s knowledge, discourse management and conversational responsiveness. The TOPICC scheme rates six categories or domains of pragmatic skills on a four-point scale: (1) reciprocity and turn-taking, (2) taking account of listener’s knowledge, (3) verbosity, (4) topic management, (5) discourse style and (6) response behaviour (0, ‘never’ to 3, ‘very frequent/always’).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the research was to examine children’s (1) ability to take listener’s knowledge into account, (2) discourse management skills, and (3) responsiveness and elaboration to the ongoing verbal exchange. All of these conversational subskills were assessed twice during middle childhood by means of (a) participation and assertiveness indexes following Bishop, Chan, Adams, Hartley, and Weir (2000), and (b) the Targeted Observation of Pragmatics in Children’s Conversation (TOPICC; Adams, Gaile, Freed, & Lockton, 2010), a four-point scale to evaluate conversational behaviours at a global level in several subcategories. Emphasis was on the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…There are isolated reports of cases with SCD who benefited from individualized therapy 61 as well as effects of therapy targeted on social communication and play in preschoolers with ASDs. 62 Data from animal models and early clinical trials suggest that novel and existing compounds, including N -methyl-D-aspartate modulators, gamma-aminobutyric acid agonists, metabotropic glutamate receptor antagonists, and neuropeptides, may enhance social communication/function in ASD.…”
Section: Treatments For Scdmentioning
confidence: 99%